Evaluasi keandalan konverter DC-DC Buck-Boost dengan pendekatan metode FMEA (Failure Mode and Effect Analysis) - Ramadhani, Ramadhani; Wiryajati, I Ketut; Citarsa, Ida Bagus Fery (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to evaluate the reliability of the DC-DC buck-boost converter using the Failure Mode and Effect Analysis (FMEA) method. The analysis was conducted to identify potential failures, impacts, and risks of key components such as MOSFETs, electrolytic capacitors, inductors, diodes, and control ICs. The results indicate that the control IC has the highest Risk Priority Number (RPN) of 16.87, followed by the MOSFET with an RPN of 11.87, making these two components the main priorities for risk mitigation. Meanwhile, electrolytic capacitors (RPN 4.7), inductors (RPN 4), and diodes (RPN 3.47) exhibit lower risks but still require regular monitoring. The suggested improvements include adding voltage protection, enhancing component cooling, and adjusting switching frequency to optimize inductor performance. This research demonstrates that the FMEA method can enhance system reliability by identifying critical failures and providing appropriate recommendations for risk reduction efforts. By implementing these measures, the DC-DC buck-boost converter is expected to operate more stably, efficiently, and have a longer lifespan